Effect of cd-rom on information accessibility and retrieval at University of Ibadan library (1999)
The University of Ibadan Library had experienced persistent short age of periodicals books and other techicaliterature. This is the same experience that libraries all over Nigeria is currently undergoing. The introduction of CD-ROM in this libraries has being a relief to this problem. There is an increased awareness and improved patronage of this technology among different categories of researchers including students in the library over the years. Though level of Computer literacy of users is still very low nevertheless CD-ROM has provided more access to Information and retrieval. This is however in the face of some constraints such as inadequate infractures, unreliable but pertinent electricity supply etc. Solution to these constraints are suggested.